Regional and subcellular changes in the concentration of 5-hydroxytryptamine and 5-hydroxyindoleacetic acid in the rat brain caused by hydrocortisone, DL-α-methyltryptophan l-kynurenine and immobilization - Curzon, G. (1971)
1. In agreement with previous findings on whole brain, the intraperitoneal injection of hydrocortisone, DL-α-methyltryptophan or L-kynurenine decreased the concentrations of 5-hydroxytryptamine (5-HT) and 5-hydroxy-indoleacetic acid (5-HIAA) in different regions of the rat brain. 2. Hydrocortisone caused similar decreases in the concentrations of both 5-HT and 5-HIAA, suggesting decreased 5-HT synthesis. 3. Changes in the concentration of 5-HIAA after hydrocortisone corresponded significantly to those after α-methyltryptophan. Changes in the concentration of 5-HT did not correspond, possibly due to falsely high 5-HT values because of interfering material derived from α-methyltryptophan. 4. In general, kynurenine caused larger decreases in the concentration of 5-HT than in the concentration of 5-HIAA. 5. In agreement with previous findings with whole brain, immobilization of rats for 5 h decreased the concentration of 5-HT and increased that of 5-HIAA in most brain regions. 6. The order of the percentage decreases in the concentrations of 5-HIAA 6 h after hydrocortisone injection was, in decreasing order: hypothalamus, striatum, cerebellum, mid-brain, pons + medulla and cortex. The percentage increases after immobilization for 5 h were in the reverse order. 7. The differences between the percentage decreases in the concentration of 5-HIAA after hydrocortisone and the percentage increases after immobilization were very similar in all regions except the hypothalamus. This is consistent with immobilization stress increasing the firing rate of 5-hydroxytryptaminergic neurones similarly in different regions. 8. During the first 3 h of immobilization the concentrations of 5-HIAA in the hypothalamus and in the rest of the brain increased approximately in parallel. Between 3 and 5 h, 5-HIAA returned to control concentrations in the hypothalamus while continuing to rise in the rest of the brain. 9. Relative changes in the concentration of 5-HT in particulate and supernatant fractions after the various treatments were comparable except 2 h after kynurenine injection when the concentration 5-HT fell in the particulate but not in the supernatant fraction. The concentration of 5-HT did fall in the latter, though more slowly than in the former fraction, suggesting a concentration of amine synthesizing organelles in particulate material.